Coumarin-3-carboxylic acid derivatives as potentiators and inhibitors of recombinant and native N-methyl-d-aspartate receptors - Irvine, Mark W.; Costa, Blaise M.; Volianskis, Arturas; Fang, Guangyu; Ceolin, Laura; Collingridge, Graham L.; Monaghan, Daniel T.; Jane, David E. (Neurochemistry international, 2012)
► Coumarins based on the negative allosteric modulator UBP608 inhibit cloned NMDARs. ► 6,8-Dibromo- and 6,8-diiodo-coumarin-3-carboxylate were the most potent inhibitors. ► The coumarin UBP714 potentiates recombinant NMDAR responses. ► UBP714 potentiated NMDAR but not AMPAR EPSPs in the CA1 region of the hippocampus. ► UBP714 may be a template for the development of cognitive enhancing drugs. N-Methyl-d-aspartate receptors (NMDARs) are known to be involved in a range of neurological and neurodegenerative disorders and consequently the development of compounds that modulate the function of these receptors has been the subject of intense interest. We have recently reported that 6-bromocoumarin-3-carboxylic acid (UBP608) is a negative allosteric modulator with weak selectivity for GluN2A-containing NMDARs. In the present study, a series of commercially available and newly synthesized coumarin derivatives have been evaluated in a structure–activity relationship (SAR) study as modulators of recombinant NMDAR activity. The main conclusions from this SAR study were that substituents as large as iodo were accommodated at the 6-position and that 6,8-dibromo or 6,8-diiodo substitution of the coumarin ring enhanced the inhibitory activity at NMDARs. These coumarin derivatives are therefore excellent starting points for the development of more potent and GluN2 subunit selective inhibitors, which may have application in the treatment of a range of neurological disorders such as neuropathic pain, epilepsy and depression. Surprisingly, 4-methyl substitution of UBP608 to give UBP714, led to conversion of the inhibitory activity of UBP608 into potentiating activity at recombinant GluN1/GluN2 receptors. UBP714 also enhanced NMDAR mediated field EPSPs in the CA1 region of the hippocampus. UBP714 is therefore a novel template for the development of potent and subunit selective NMDAR potentiators that may have therapeutic applicability in the treatment of patients with cognitive deficits or schizophrenia.